A meta-analysis of evolution of gastronomy and culinary education research published in top-tier culinary, hospitality, and tourism journals. Issue 1 (2nd January 2021) - Okumus, Bendegul
ABSTRACT: The present study offers a meta-analysis of gastronomy and culinary education research published in top-tier culinary, hospitality, and tourism academic journals. This study found 41 articles related to gastronomy and culinary education (GCE) research published in 16 top-tier academic journals. Each of these 41 articles was systematically analyzed and evaluated by focusing on several topics related to GCE. Overall, the meta-analysis of these articles shows that there has been limited research published on GCE in top-tier culinary, hospitality, and tourism journals. Of those 41 articles reviewed, empirical studies with quantitative and qualitative methods were more frequent. There is a clear scarcity in total publication numbers and use of advanced research methods in GCE research published in top-tier culinary, hospitality, and tourism journals. This is the first study to offer an in-depth analysis of GCE research in top-tier culinary, hospitality, and tourism journals.